From the Screen to the State: How Science Fiction Films Inspire and Influence Science and Technology Policy - Hooman Shababi (National Research and Innovation Agency, Indonesia, 2025)
This article explores how science fiction films shape science and technology policy by constructing public imaginaries and envisioning future scenarios. Grounded in the Narrative Policy Framework and the theory of sociotechnical imaginaries, the study employs narrative analysis to examine selected films—Interstellar, Gattaca, Her, and The Martian—focusing on how they portray ethical dilemmas, technological visions, and sociopolitical themes relevant to policy discourse. The findings reveal recurring narrative tropes such as techno-utopianism, existential risk, space exploration, and post-human futures, which inform how societies imagine innovation, regulation, and governance. Rather than treating films as mere reflections of technological change, the article argues that they actively shape collective hopes, fears, and expectations around emerging technologies. These cinematic narratives function as cultural tools that frame policy discussions on artificial intelligence, genetic engineering, and climate technologies. By connecting popular culture with policy analysis, the article highlights the role of science fiction in the anticipatory governance of science and technology, offering an interdisciplinary contribution to Science and Technology Studies (STS).